Lagenorhynchus obliquidens Gill 1865 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lagenorhynchus obliquidens Gill, 1865. Proc. Acad. Nat. Sci. Phila., 17: 177. TYPE LOCALITY: U.S.A., California, near San Francisco. DISTRIBUTION: North Pacific, from Alaska and Aleutian Isis, to Baja California and from Kamchatka to Taiwan. COMMENT: L. thicolea (Gray, 1946) may be the correct name for this species; see Hall, 1981:889. May be a Northern Hemisphere form of obscurus (RLB and WFP). PROTECTED STATUS: CITES - Appendix II as Order Cetacea. ISIS NUMBER: 5301411002012005001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Cetacea, pp. 290-304 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 293, DOI: 10.5281/zenodo.7352983